2017
DOI: 10.1177/0896920517715765
|View full text |Cite
|
Sign up to set email alerts
|

Polar Opposites? NGOs, Left Parties and the Fight for Social Change in Nepal

Abstract: In the early 1990s, when NGOs were rising to prominence as an ostensible

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, they suggested that NGOs can play a significant role in bridging the government, markets, and citizens. Ismail () argued that foreign‐funded NGOs are unlikely to counter neoliberal development. Tanaka () argued that the majority of NGOs in the country belong to a group of elites and very rarely include members from excluded, marginalised, and underprivileged communities.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, they suggested that NGOs can play a significant role in bridging the government, markets, and citizens. Ismail () argued that foreign‐funded NGOs are unlikely to counter neoliberal development. Tanaka () argued that the majority of NGOs in the country belong to a group of elites and very rarely include members from excluded, marginalised, and underprivileged communities.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, with the decline of secure, formal unionized workforces, there is a recognition that mainstream unions are increasingly compelled to try to adopt new strategies to engage with the struggles of informal, unorganized, and gig workers (Eaton et al., 2017). Simultaneously, there is a growing acknowledgment that NGOs engaged with informal workers cannot take the place of unions (Domínguez Reyes & Quintero Ramírez, 2019): the focus of NGOs on alternative income generating activities at the expense of workers' rights (RoyChowdhury, 2005), with depoliticizing agendas tied to funding from donor governments in the Global North, tends to delegitimize labor insurgency (Ismail, 2018; Siddiqi, 2020).…”
Section: Informality Precarity and Organizing Among Women Workersmentioning
confidence: 99%
“…It resulted in no significant changes in its policy within and outside the country, especially the relations with India (Kumar, 2016). The civil war ended in 2006 after all political parties in Nepal, including the Maoist movement, agreed to resolve the conflict peacefully and bring the country into a republic in 2008 (Ismail, 2018).…”
Section: Domestic Political Change In Nepalmentioning
confidence: 99%